Survival of mature T cells in the periphery is intrinsically dependent on GIMAP1 in mice. Issue 1 (25th November 2016) - Datta, Preeta; Webb, Louise M.C.; Avdo, Inxhina; Pascall, John; Butcher, Geoffrey W.
Abstract : Without expression of GIMAP1, mature T lymphocytes fail to survive. This was demonstrated in vitro and in vivo by transfer of T cells followed by chemically induced gene ablation. Cell death is preceded by mitochondrial depolarization and activation of caspase‐8. Abstract : An effective immune system depends upon the survival of mature T cells in the periphery. Members of the GIMAP family of GTPases have been proposed to regulate this homeostasis, supported by the paucity of peripheral T cells in rodents deficient for either GIMAP1 or GIMAP5. It is unclear whether this lack of T cells is a consequence of an ontological defect, causing the thymus to generate and export T cells incapable of surviving in the periphery, or whether (alternatively or additionally) mature T cells intrinsically require GIMAP1 for survival. Using the ER T2 Cre + transgene, we conditionally deleted Gimap1 in C57BL/6 mice and demonstrate that GIMAP1 is intrinsically required for the survival of mature T cells in the periphery. We show that, in contrast to GIMAP5, this requirement is independent of the T‐cells' activation status. We investigated the nature of the survival defect in GIMAP1‐deficient CD4 + T cells and show that the death occurring after GIMAP1 ablation is accompanied by mitochondrial depolarization and activation of the extrinsic apoptotic pathway. This study shows that GIMAP1 is critical for maintaining the peripheral T‐cell pool in mice and offers a potent target for the treatment of T‐cell‐mediated diseases.